(untitled) (Conferencea, 2022)
The article highlights the most important components in the structure of creativity of undergraduate students in pedagogical education to improve the competent approach to creative thinking in students, different aspects of creative and reproductive thinking. qualities such as imagination, fantasy, emotional kindness, and benevolence that are needed for future educators are also shown.